Temporal variation of Black Carbon concentration using Aethalometer observations and its relationships with meteorological variables in Karachi, Pakistan. (May 2017) - Bibi, Samina; Alam, Khan; Chishtie, Farrukh; Bibi, Humera; Rahman, Said
Abstract: Black Carbon (BC) mass concentration was measured continuously for every five-minute interval with ground-based Aethalometer at an urban site in Karachi for the period from 2006 to 2008. In this study, the temporal (diurnal, monthly and seasonal) variations of BC and its relationship with meteorological variables were analyzed. Monthly averaged concentrations of BC ranged from 2.2 to 12.5 µg/m 3, with maximum in the month of January 2007 and minimum in the month of June 2006. BC showed higher concentrations during the months of January, February and November while lower during the months of May, June, July and August throughout the years. It also displayed comparatively high concentrations during winter and postmonsoon, while moderate during premonsoon and low during summer. Diurnal analysis of BC concentration showed sharp peaks between 07:00 and 09:00 LST and again around 22:00 during all the months. Moreover, the relationship between BC concentration and meteorological variables such as Temperature (Temp), Relative Humidity (RH), Wind Speed (WS), Visibility (VIS) and RainFall (RF) was found and it was observed that BC concentration showed an inverse relationship with all these meteorological variables. Finally, the analysis of the Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) cluster trajectories revealed that almost all the clusters were originating from southwest of the study site. Highlights: BC was highest in January while lowest in June. BC was higher in winter and postmonsoon, moderate in premonsoon and low in summer. Morning peaks were more pronounced than evening peaks. BC presented inverse relationships with all meteorological variables. Cluster trajectories revealed that most of the air masses arrived from Middle East.